Florescendo mentes: curso de formação profissional para professores acerca da ideação suicida em adolescentes - Barbosa, Ane Caroline de Carvalho (2023)
This work presents the conclusive technical report of the Professional Training Course for teachers on suicidal ideation in adolescents, linked to the Department of Education of the city of Piripiri-PI and the Professional Postgraduate Program in Psychology and Public Policies at the Federal University of Ceará – PPGPPPP, Sobral campus. The objective was to develop a Professional Training Course to support and manage suicidal ideation in adolescents with the teaching public. The content was formulated from two moments, the first moment refers to the availability of a form on Google Forms aimed at teachers from the municipal network of Piripiri-PI and the second moment occurred during the implementation of the professional training course on ideation suicide for teachers. The intervention took place between August and September 2023. 25 female and 10 male teachers participated in the Professional Training Course in person. Through an active methodology, with questions that mobilize discussion, participants were able to share experiences about understandings related to suicidal ideation in adolescents in the school context. The evaluation pointed out that the professional training course contributed in a relevant way, given how much the theme is present in daily work, indicating the need for greater discussion on the topic as a way of transforming practices in education and health, in addition to enabling new care strategies. Contact with professionals highlights the importance of continuous training and the need for psychologists to work in a school environment, as well as the regular participation of the family as tools for preventing suicidal ideation and promoting health.